2005
DOI: 10.1007/s00134-005-2572-x
|View full text |Cite
|
Sign up to set email alerts
|

Surface triggering receptor expressed on myeloid cells 1 expression patterns in septic shock

Abstract: The specificity of TREM-1 regulation by infection is highlighted. Moreover, surface TREM-1 expression on monocytes may prove useful in allowing the follow-up of septic patients during the course of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
73
3
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 19 publications
6
73
3
1
Order By: Relevance
“…TREM-1 expression is increased during both acute ( 49,50 ) and chronic infl ammation ( 51 ). Moreover, a soluble form of TREM-1 was detected in the blood sample of human patients with infl ammatory disorders, such as sepsis ( 52 ), pneumonia ( 53 ), acute pancreatitis ( 54 ), and peptic ulcer disease ( 55 ). Very recently, Kuai et al reported that TREM-1 expression is increased in the synovium of RA patients ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…TREM-1 expression is increased during both acute ( 49,50 ) and chronic infl ammation ( 51 ). Moreover, a soluble form of TREM-1 was detected in the blood sample of human patients with infl ammatory disorders, such as sepsis ( 52 ), pneumonia ( 53 ), acute pancreatitis ( 54 ), and peptic ulcer disease ( 55 ). Very recently, Kuai et al reported that TREM-1 expression is increased in the synovium of RA patients ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the DAP12-associated receptor TREM-1 is up-regulated upon monocyte and neutrophil activation by fungus and extracellular bacteria, and especially by LPS and lipoteichoic acid which are microbial components, but not nonbacterial TLR ligands (7,10,23). TREM-1 is also up-regulated in neutrophils of patients with pneumonia (24) and in monocytes of patients suffering from septic shock (23,25) indicating a role in the detection and response to microbial infection. In contrast, hOSCAR expression did not change in the conditions of neutrophil activation analyzed in this study, suggesting that the physiologic regulation of hOSCAR reactivity during inflammatory responses may depend on availability or regulation of the expression of the counter-receptor.…”
Section: Discussionmentioning
confidence: 99%
“…TREM-1 expression is up-regulated in myeloid cells after LPS stimulation (45) or during sepsis (49). TREM-2 expression is associated with regulating myeloid lineage development (50).…”
Section: Discussionmentioning
confidence: 99%